1986
DOI: 10.1128/mcb.6.11.3826
|View full text |Cite
|
Sign up to set email alerts
|

Microdissection of and microcloning from the short arm of human chromosome 2.

Abstract: A bank of cloned DNA sequences from the distal half of the short arm of human chromosome 2 was generated by using microdissection and microcloning techniques. DNA was purified from 106 chromosomal fragments, manually dissected from peripheral lymphocytes in metaphase, and cloned into the EcoRI site of XgtlO. A total of 257 putative recombinants were recovered, of which 41% were found to contain human inserts. The mean insert size was 380 base pairs (median size, 83 base pairs), and fewer than 10% of the clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…This technique was then applied to mouse to obtain 212 microclones from the proximal half of chromosome 17 containing the t-complex [56]. Then, it was extended to human chromosomes [3]. However, at that time, studies were mainly focusing on some chromosomes that are easily identifiable by their configuration, such as the X chromosome of mouse [5] and chromosome 2 of human [3].…”
Section: Chromosome Recognition--the Prerequisite Of This Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This technique was then applied to mouse to obtain 212 microclones from the proximal half of chromosome 17 containing the t-complex [56]. Then, it was extended to human chromosomes [3]. However, at that time, studies were mainly focusing on some chromosomes that are easily identifiable by their configuration, such as the X chromosome of mouse [5] and chromosome 2 of human [3].…”
Section: Chromosome Recognition--the Prerequisite Of This Techniquementioning
confidence: 99%
“…Then, it was extended to human chromosomes [3]. However, at that time, studies were mainly focusing on some chromosomes that are easily identifiable by their configuration, such as the X chromosome of mouse [5] and chromosome 2 of human [3]. After the advent of G-banding technique, which makes the identification of human and animal chromosomes easier, and PCR technique, the chromosome microdissection and microcloning technique was extensively used in human and animal genomics research [38,46,47,49,74,75].…”
Section: Chromosome Recognition--the Prerequisite Of This Techniquementioning
confidence: 99%
“…The BCM1 locus, coding for a 40-45 kD B-cell cell surface glycoprotein primarily expressed in mitogen treated lymphocytes and related to the immunoglobulin gene super family, has been localized to lcen-q32 with somatic cell hybrids (Barton et al HGM9). Loci for two T lymphocyte antigens, CD1 (Calabi and Milstein 1986) and CD2 (Brown et al 1986), have been assigned to chromosome 1 by somatic cell hybrid analysis with regional localization of CD2 to lp l3 by in situ hybridization. McBride et al (HGM9) have assigned sequences identified by a cDNA clone for human poly (ADP-ribose) polymerase (PPOL), a chromatin associated enzyme, to chromosomes lq, 13, and 14.…”
mentioning
confidence: 99%
“…3 Introdução__________________________________________________________________ A técnica de microdissecção cromossômica foi introduzida inicialmente em citogenética humana (Bates et al, 1986), com a construção de uma biblioteca do cromossomo dois usando-se muitos fragmentos cromossômicos dissecados de metáfases não coradas ou bandeadas. Posteriormente, Ludecke et al (1989) A técnica de micro-FISH permite a localização cromossômica de sequências específicas, a detecção de anormalidades cromossômicas e a "pintura" de cromossomos inteiros (Trask, 1991).…”
Section: Considerações Sobre a Citogenética De Peixes E A Microdissecunclassified
“…Do mesmo modo, a aplicação de fluorocromos e endonucleases de restrição, aliada as técnicas de coloração convencional, trouxe esclarecimentos acerca dos mecanismos envolvidos na formação do cromossomo Y em Eigenmannia sp2, corroborando com uma hipótese anteriormente postulada, que sugeria que nessa espécie a diferenciação sexual estaria realmente relacionada a regiões cromossômicas GC positivas (Almeida-Toledo et al, 2000b). O estudo sistematizado de outros grupos de peixes, como os efetuados em Hoplias malabaricus (síntese em Bertollo et al, 2000; Born e Bertollo, 2002), Astyanax (síntese em Kavalco, 2008), Corydoras (Oliveira et al, 1988b;, Triportheus (Artoni et al, 2001; Artoni e Bertollo, 2002;Diniz et al, 2008) dentre outros, também tem trazido importantes informações cariotípicas, muitas vezes esclarecedoras de questões genético-evolutivas relacionadas aos peixes Neotropicais.3 Introdução__________________________________________________________________ A técnica de microdissecção cromossômica foi introduzida inicialmente em citogenética humana (Bates et al, 1986), com a construção de uma biblioteca do cromossomo dois usando-se muitos fragmentos cromossômicos dissecados de metáfases não coradas ou bandeadas. Posteriormente, Ludecke et al (1989) A técnica de micro-FISH permite a localização cromossômica de sequências específicas, a detecção de anormalidades cromossômicas e a "pintura" de cromossomos inteiros (Trask, 1991).…”
unclassified